Biodegradable hypoxia biomimicry microspheres for bone tissue regeneration. (February 2020) - Hadidi, Lina; Constantin, Justine; Dalisson, Benjamin; Vieira, Daniela; Drager, Justin; Harvey, Edward; Merle, Geraldine
The iron chelator deferoxamine is a hypoxia biomimicry and has received interest as a potential therapeutic in tissue engineering and regenerative medicine. Recently, local injection of this iron chelator deferoxamine has proven to increase bone healing through the activation of the hypoxia-inducible factor-1 signaling pathway that augments angiogenesis and osteogenesis. Repeated injections of deferoxamine are required to achieve local therapeutic levels at fracture site. To achieve local therapeutic levels at fracture site without the use of multiples injections and associated pain and infection issues, we designed and prepared polymeric microspheres made of polycaprolactone and poly(ethylene oxide), in which deferoxamine was encapsulated, via a melting process. The application of this process has enabled to obtain spheres of different poly(ethylene oxide) concentrations for optimizing the drug release rate. The effective local release carrier offers a predetermined rate that can mimic the effect of repeated deferoxamine injections over a 14-day period to selectively stimulate bone repair and thus improve the biological performance to the point where ideally synthetics begin to challenge autograft dominance as the bone replacement of choice.